Pengaruh Pembiayaan Mudharabah, Musyarakah, Murabahah, dan Ijarah terhadap Return on Equity (ROE) Bank BCA Syariah Periode 2018–2022 - Permana, Daffa Abdi; Fatoni, Ahmad (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2025)
This study aims to examine the effect of mudharabah, musyarakah, murabahah, and ijarah financing on the return on equity (ROE) of Bank BCA Syariah. This research employs a quantitative approach with a saturated sampling technique. Secondary data were obtained from the quarterly financial reports of Bank BCA Syariah for the period 2018–2022. Data were analyzed using classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination with SPSS v23. The results show that, partially, mudharabah, musyarakah, and ijarah financing have no significant effect on ROE, while murabahah financing has a positive and significant effect on ROE. Simultaneously, the four financing variables do not have a significant effect on ROE.